Digital inclusion and urban-rural integration: Mechanisms and regional heterogeneity in China - Ximing Qiu; Ming Yu; Xia Chen (PLoS ONE, 2026)
Although digital inclusion is globally recognized as a key pathway to equitable development, rigorous empirical evidence on its specific mechanisms and regionally varying effects in driving urban-rural integration in developing countries remains scarce. To fill this gap, this study employs a fixed-effects model and robustness checks to analyze the impact of digital inclusion on urban-rural integration, using evidence from China. The findings show that digital inclusion enhances urban-rural integration by reducing information asymmetry, improving access to education and healthcare resources, and fostering industrial convergence. However, digital inclusion exerts a significant positive effect on urban-rural integration in eastern and central China, but has no significant effect in western China. These findings challenge the conventional view that digital policies have a homogeneous impact and emphasize the need for spatially differentiated interventions. By integrating an analysis of these mechanisms with an examination of regional disparities, this research advances theoretical understanding of digital inclusion’s societal effects and provides critical empirical support and policy insights for developing countries aiming to develop regionally differentiated digital inclusion strategies.